Perbaikan Asupan Makan Pada Pasien Tuberkulosis Anak Usia 11 Tahun Setelah dilakukan Pendekatan Kedokteran Keluarga Secara Holistik - Luthfi Aulia Oktofani; Reni Zuraida (CV. Jasa Sukses Abadi, 2021)
The number of TB cases in Indonesia in 2019 reached 543,874 cases, of which 11.92% of the total cases in Indonesia were aged 0-14 years. In the management of TB patients, especially TB in children, it really needs cooperation from various parties, one of which is the role of the family doctor. The study is Case Report. Primary data was obtained through history taking and physical examination, filling out family folders, and filling in patient files. Assessment was carried out based on the initial holistic diagnosis and end of the visit qualitatively and quantitatively using foodrecall. Based on a holistic diagnosis, patients complain of coughing that does not improve for 1 month and has weight loss. The patient is concerned that the illness cannot be cured and can spread to other people. Patient perceives that TB is dangerous diseases. Patient hopes the child can get the treatment completely so that he can recover again. Patients diagnosed with new case of pulmonary tuberculosis in child that diagnosed clinically based on the results of history, physical examination, and rontgen. The patient has a history of contact with child TB. The diagnosis of pediatric pulmonary TB in this case is in accordance with the theory and critical analysis of current research, using TB scoring system. The management given is in accordance with the guidelines, there are changes in behavior and knowledge of healthy life and dietary habit in patients and families of patients after an intervention based on evidence based medicine that is patient centered, family approach.